POTENSI DAN PEMANFAATAN TANAMAN BAMBU PADA LAHAN MASYARAKAT DI DESA KADING KABUPATEN BARRU - Miftahul Jannah; Baharuddin Baharuddin; Ira Taskirawati (Forestry Faculty of Universitas Hasanuddin, 2019)
Non-wood forest products (NTFPs) are the result of the forestry sector are still very much needed by the world and can be an opportunity to add value to the economy, especially in the forestry sector. This study aims to determine the potential and utilization of bamboo on community land in Kading Village, Tanete Riaja District, Barru Regency. There are two data collected in this study; they are potential data and bamboo plant utilization data. Potential data collection in this study was carried out in three stages, namely mapping the distribution point of a bamboo clump, collecting data on an area of farmer's garden that has bamboo, and counting the number of bamboo groves on the respondent's bamboo land. Candid interviews with 30 bamboo landowners obtained the data on the use of bamboo plants. The total area of community land covered with bamboo in Kading Village is 7.29 ha with 250 clumps consisting of 2,203 bamboo shoots, 5,345 young bamboo, and 4,532 old bamboos.